Application of artificial intelligence in international decision-making processes in the healthcare industry. (3rd April 2023) - Díaz, Christian; Neubert, Michael
The purpose of this qualitative multiple case study is to explore the use of artificial intelligence (AI) in international decision-making processes in the healthcare industry. The results of the research suggest the following: 1) efficiency improvement, quality enhancement, decision support, big data analysis, cost reduction, behaviour monitoring, and prediction were identified as factors that foster AI use in healthcare's sector decision-making processes; 2) delegability in AI for decision-making processes in the sector responds to two central drivers: difficulty and trust; 3) a preference towards a configuration where humans take the final decision instead of a AI was observed. The limitations are mainly connected to the selected methodology, participants and use cases, so further research is required to support generalisability. The results presented may be helpful in practice to increase the current understanding of the main drivers involved in the AI application for decision-making processes in the healthcare industry.